Endothelial Dysfunction and Oxidative Stress in Patients with Severe Coronary Artery Disease: Does Diabetes Play a Contributing Role? - Alexandra Maria Boieriu; Cezar Dumitrel Luca; Carmen Daniela Neculoiu; Alina Bisoc; Diana Țînț (Medicina)
Background and Objectives: Endothelial dysfunction (ED) and oxidative stress play major contributions in the initiation and progression of atherosclerosis. Diabetes is a pathological state associated with endothelial damage and enhanced oxidative stress. This study evaluated endothelial dysfunction and oxidative stress in patients with severe coronary artery disease (CAD) undergoing coronary artery bypass graft (CABG) surgery, comparing those with and without type 2 diabetes mellitus (T2DM). Materials and Methods: We included 84 patients with severe coronary artery disease (33 of whom had type 2 diabetes mellitus) who underwent clinical assessments, ultrasound, and coronaryangiography. The SYNTAXI score was calculated from the coronaryangiogram. Blood samples were collected to measure plasma serotonin (5-HT; SER) levels, as well as levels of superoxide dismutase 1(SOD-1) and lectin-like oxidized low-density lipoprotein receptor-1(LOX-1) to assess oxidative stress. Brachial flow-mediated dilation (FMD) was used as a surrogate for endothelial dysfunction (ED),along with serum concentrations of 5-HT. Results: The coronary atherosclerotic burden, assessed using the SYNTAX I score, was more severe in patients with CAD and associated T2DM compared to those with CAD without T2DM (30.5 (17–54) vs. 29 (17–48); p = 0.05). The SYNTAX score was found to be positively correlated with T2DM (p = 0.029; r = 0.238).ED measured by FMD was associated with T2DM (p = 0.042; r = −0.223), with lower FMD measurements in T2DM patients when compared with individuals without this pathology (2.43% (0.95–5.67) vs. 3.46% (1.02–6.75); p = 0.079). Also, in the studied population, T2DM was correlated with serum 5-HT levels (764.78 ± 201 ng/mL vs. 561.06 ± 224 ng/mL; p < 0.001; r = 0.423), with higher plasma circulating levels of 5-HT in patients with T2DM. No statistically significant differences for oxidative stress markers (SOD-1 and LOX-1) were obtained when comparing T2DM and non-T2DM patients with severe CAD. Conclusions: ED (as assessed by brachial FMD and serum 5-HT) is more severe in in diabetic patients with severe CAD scheduled for CABG surgery, while oxidative stress (as evaluated through serum SOD-1 and LOX-1 concentrations) was not influenced by the presence of T2DM in this specific population. The most important finding of the present study is that circulating 5-HT levels are markedly influenced by T2DM. 5-HT receptor-targeted therapy might be of interest in patients undergoing CABG, but further studies are needed to confirm this hypothesis.